The Relationship Between Dietary Intake and Parental Support with Child Cooking Involvement in a Youth Population (FS16-03-19) - Asigbee, Fiona (Curr Dev Nutr, 2019)
OBJECTIVES: This study assessed how child cooking involvement (CCI) and parental support in food preparation (PS) are related to vegetable preference (VP), vegetable intake (VI), and fruit intake (FI) in children participating in the Texas, Grow! Eat! Go! (TGEG) randomized controlled trial. METHODS: Baseline data from the TGEG intervention, conducted in 28 low-income, primarily Hispanic schools across Texas, was used for this study, and included 1325 3(rd) grade students and their parents. Schools were assigned to: (1) control group; (2) school garden intervention [Learn, Grow, Eat & Go! (LGEG)]; (3) physical activity intervention [Walk Across Texas (WAT)]; or (4) combined group (LGEG plus WAT). Height (via stadiometer), weight (via Tanita scale), dietary intake and CCI (via child questionnaire), and PS (via parent questionnaire) were collected. General Linear Models examined variations in baseline VP, VI, and FI with baseline CCI and PS. A priori covariates for all analyses included: TGEG treatment group, age, sex, and ethnicity. RESULTS: Students were 49.2% male and 42.4% Hispanic with a mean age of 8.3 ± 0.6; 78.3% of the population had overweight/obesity. Children who never cooked with their families preferred fewer vegetables than children who sometimes/always cooked with their parents (7.0 ± 0.6 vs. 8.7 ± 0.5 and 9.4 ± 0.5 vegetables, respectively; P < 0.001). Children who never cooked with their families ate less vegetables than children who sometimes/always cooked with their parents (1.9 ± 0.4 vs. 2.6 ± 0.3 and 3.5 ± 0.3 servings/day, respectively; P = 0.003 and P = 0.000, respectively). Children who never cooked with their families ate less fruit than children who sometimes/always cooked with their parents (1.2 ± 0.2 vs. 1.5 ± 0.1 and 2.09 ± 0.1 servings/day, respectively; P < 0.001). CONCLUSIONS: Interventions including family cooking activities with children may be an effective way to increase vegetable preference and intake, and fruit intake, especially in high-risk, minority children. FUNDING SOURCES: The research was supported by funding from the USDA Agriculture and Food Research Initiative, (grant 2011-68001-30138).